2015
DOI: 10.1007/s00259-015-3047-0
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytosis precedes amyloid plaque deposition in Alzheimer APPswe transgenic mouse brain: a correlative positron emission tomography and in vitro imaging study

Abstract: PurposePathological studies suggest that neuroinflammation is exacerbated by increased beta-amyloid (Aβ) levels in the brain early in Alzheimer’s disease (AD). The time course and relationships between astrocytosis and Aβ deposition were examined using multitracer in vivo positron emission tomography (PET) imaging in an AD transgenic mouse model, followed by postmortem autoradiography and immunohistochemistry analysis.MethodsPET imaging with the amyloid plaque tracer 11C-AZD2184 and the astroglial tracer 11C-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
99
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(123 citation statements)
references
References 60 publications
11
99
0
Order By: Relevance
“…In fact, the major increase in Aβ deposition was found between 8 and 12 months, while MAO-B levels appeared to be elevated already at 8 months. These results are also in line with a previous study that reported elevated [ 11 C]DED binding in APP swe mice compared with WT mice [30]. Somewhat contradictory to the present study, this previous study showed higher [ 11 C]DED binding in young 6-month-old APP swe mice compared with older mice.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In fact, the major increase in Aβ deposition was found between 8 and 12 months, while MAO-B levels appeared to be elevated already at 8 months. These results are also in line with a previous study that reported elevated [ 11 C]DED binding in APP swe mice compared with WT mice [30]. Somewhat contradictory to the present study, this previous study showed higher [ 11 C]DED binding in young 6-month-old APP swe mice compared with older mice.…”
Section: Discussionsupporting
confidence: 86%
“…The biochemical quantification of GFAP with ELISA confirmed the results obtained with immunohistochemistry and indicated that increased GFAP levels were a consequence of, or at least mirrored, the Aβ accumulation. These results are also supported by the previous studies in APP swe mice and on post mortem human brain tissue [30,42]. Another preclinical study, conducted in APP/PS1 mice, focusing on GABA function reported low degree of co- localization of MAO-B and GFAP [43].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In particular, small-animal PET imaging of b-amyloid has been successfully established in the past few years (9,10). However, information regarding neuroinflammation in these models remains sparse and rather inconsistent (11)(12)(13).…”
mentioning
confidence: 99%